Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

4. Solve the equation: -18 = 6(2 + x)

Sagot :

[tex]~~~~~~6(2+x) = -18\\\\\implies 2+x = -\dfrac{18}6\\\\\implies 2+x = -3\\\\\implies x = -3-2\\\\\implies x =-5[/tex]

Given equation:

  • -18 = 6(2 + x)

Step-by step solution;

Simplifying the distributive property;

⇒ -18 = (6 × 2) + (6 × x)  

Further simplifying the distributive property;

⇒ -18 = (12) + (6x)

Subtracting 12 to both sides of the equation;

⇒ -18 - 12 = (12) + (6x) - 12

Simplifying both sides of the equation;

⇒ -30 = (6x)

Dividing 6 to both sides of the equation;

⇒ -30/6 = (6x)/6

-5 = x

Therefore, the value of "x" is -5.

Learn more about this topic: https://brainly.com/question/851533